Assessing e-Government systems success in Jordan (e-JC): A validation of TAM and IS Success model Validation of TAM and IS for e-Government Systems Success in Jordan - Sari, Arif; Akkaya, Murat; Abdalla, Bashar (International journal of computer science and information security, 2017)
Drawing on information systems success model and technology acceptance model, this article will examine the impact of system quality, information quality, and service quality on perceived usefulness, perceived ease of use, and citizen's attitudes toward the use of e-JC system. Data analysis involving 398 randomly selected subjects was conducted to test these propositions, general support was found for all the interactions. Results from structural equation modeling delineates that information, system and service quality of e-government influences citizens perceived ease of use and perceived usefulness, which in turn influences citizens adoption/attitudes toward use of the e-government system. The findings indorse the model of interest, and also contributes to the literature by strengthening researchers' theoretical and practical understanding of the effects of information, system, and service quality in developing e-government system.